THE INSTITUTIONALIZATION OF THE GOLONGAN KARYA (GOLKAR) PARTY IN TEBO REGENCY IN THE 2024 LEGISLATIVE ELECTIONS - Nadya Sitta Cahya Safitri; Dimas Subekti; Revi Jeane Putri; Hatta Abdi Muhammad (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2026)
This study aims to analyze the institutional consolidation of the Golkar Party in the 2024 Legislative Elections in Tebo Regency. This study uses a qualitative case study approach. This study uses primary data from in-depth interviews and secondary data from documentation. The findings of this study indicate that the institutionalization of the Golkar Party in Tebo Regency is relatively strong, particularly in terms of roots in society, level of organization, and coherence. The Golkar Party has maintained close ties with the community, built a solid organizational structure, and sustained internal cohesion through regular candidate consolidation and training. This has been a key factor in the party's success in the 2024 elections. However, weaknesses remain in the autonomy dimension, as decision-making processes are still dominated by party elites and selection mechanisms remain only partially transparent. This situation highlights a gap between democratic principles and political practices on the ground. Implications: The electoral success of political parties does not depend solely on short-term campaign strategies but also on consistent, democratic institutional strength.